Using μPIXE for quantitative mapping of metal concentration in Arabidopsis thaliana seeds - Schnell Ramos, Magali; Khodja, Hicham; Mary, Viviane; Thomine, Sebastien (Frontiers in Plant Science, 2013)
Seeds are a crucial stage in plant life. They contain the nutrients necessary to initiate the development of a new organism. Seeds also represent an important source of nutrient for human beings. Iron (Fe) and zinc (Zn) deficiencies affect over a billion people worldwide. It is therefore important to understand how these essential metals are stored in seeds. In this work, Particle-Induced X–ray Emission with the use of a focused ion beam (µPIXE) has been used to map and quantify essential metals in Arabidopsis seeds. In agreement with Synchrotron radiation X-Ray Fluorescence (SXRF) imaging and Perls/DAB staining, µPIXE maps confirmed the specific pattern of Fe and Mn localization in the endodermal and subepidermal cell layers in dry seeds, respectively. Moreover, µPIXE allows absolute quantification revealing that the Fe concentration in the endodermal cell layer reaches ~800 µg•g-1 dry weight. Nevertheless, this cell layer accounts only for about half of Fe stores in dry seeds. Comparison between Arabidopsis wild type and mutant seeds impaired in Fe vacuolar storage (vit1-1) or release (nramp3nramp4) confirmed the strongly altered Fe localization pattern in vit1-1, whereas no alteration could be detected in nramp3nramp4 dry seeds. Imaging of imbibed seeds indicates a dynamic localization of metals as Fe and Zn concentrations increase in the subepidermal cell layer of cotyledons after imbibition. The complementarities between µPIXE and other approaches as well as the importance of being able to quantify the patterns for the interpretation of mutant phenotypes are discussed.